The Role of Acehnese Women in Dealing With the Corvid-19 Pandemic Phenomenon - Alwi Alwi; Taufik Abdullah; Muhammad bin Abubakar (Master Program of Sociology, Universitas Malikussaleh,, 2022)
The phenomenon of corvid 19 is a phenomenon that affects people's social changes to get used to a new social order called the